TRANSPORTASI REALITAS TEKSTUAL: ORIENTASI KOGNITIF PADA GAME PC SHOGUN II TOTAL WAR - Dida Ibrahim Abdurrahman (ATRAT: Jurnal Seni Rupa, 2015)
Transportation textual reality premise opens understanding about the process of transformation narrative literature that paved the mentality of the realm of imagination. Object and subject to the groove of writing open representative realities that are different from the reality that was built in a movie or picture story within and directs viewers to the tendency of a uniform interpretation. In contrast to the representational reality on digital game that combines imagination with option offers interpretation and meaning. The concept of interaction has mentally close the gap between users and their medium. Keywords: Textual Reality, Literatur Transformation, Digital Game Cognitive Orientation___________________________________________________________________Premis transportasi realitas tekstual membuka pemahaman mengenai proses transformasi narasi literatur yang meretas mentalitas ranah imaji. Objek dan subjek pada alur penulisan membuka realitas-realitas representatif yang berbeda dengan realitas yang dibangun pada film atau cerita bergambar yang berjarak dan mengarahkan pemirsanya pada kecenderungan interpretasi yang seragam. Berbeda dengan realitas representasional pada game digital yang menggabungkan imajinasi dengan penawaran pilihan interpretasi dan pemaknaan. Konsep interaksinya secara mental telah mendekatkan jarak antara pengguna dan media yang digunakanya. Kata Kunci: Realitas Tekstual, Transportasi Literatur, Orientasi Kognitif Game PC